On the Problems and Directions for the Prevention of Juvenile Delinquency - ZHADAN, Vladimir N.; KAMALOVA, Galina T.; SADYKANOVA, Zhanna E.; KARIPOVA, Assel Ye. (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019, 2019)
Despite many years of experience in the crime prevention in the juvenile environment, today the problem of committing offences and crimes among juveniles has not been solved and is still one of the most relevant which makes it necessary to improve preventive measures for reducing the potential number of offenders among juveniles. The purpose of this article is to identify the most effective and efficient measures to prevent juvenile delinquency based on cross-country comparison and retrospective analysis. The leading approach in this research is a comparative and legal approach to the study of the problem which allows to identify the most effective measures. The main aspects of the positive experience of regulating the issue of research in retrospect, as well as the mistakes that have taken place, which should not be made in the future, are identified. The degree of regulation of the issue at the international level is characterized. A comparative analysis of the system of agencies and institutions for the crime prevention among juveniles in Russia, Kazakhstan and Ukraine, as well as the regulation of the issue in Russia and foreign countries, is conducted. Recommendations are given regarding the directions of juvenile delinquency prevention, as well as statistical data on the countries in the dynamics. The development of recommendations and the solution of this problem should be carried out not only at the theoretical but also at the practical level and this will allow to create in the future favorable conditions for the development of the younger generation, the formation of favorable behavior and active participation in art, cultural, sports and social activities.